An Incentive Dynamic Programming Method for the Optimization of Scholarship Assignment - Di Huang; Yu Gu; Hans Wang; Zhiyuan Liu; Jun Chen (Discrete Dynamics in Nature and Society)
Scholarship assignment is an operations management problem confronting university administrators, which is traditionally solved based on administrators’ personal experiences. This paper proposes an incentive method inspired by dynamic programming to replace the traditional decision-making process in the scholarship assignment. The objective is to find the optimal scholarship assignment scheme with the highest equity while accounting for both the practical constraints and the equity requirement. Moreover, with the proposed method, the scholarship assignment avoids time- and energy-consuming application processes conducted by students. A solution algorithm is used to find feasible assignment schemes by iteratively solving a series of knapsack subproblems based on dynamic programming and adjusting the monetary value of a unit score. The optimal assignment scheme can then be screened out by applying the Gini coefficient for quantifying the equity of each feasible scheme. A numerical case is investigated to illustrate the applicability of the proposed method and solution algorithm. The results indicate that the proposed method is an efficient tool to assign scholarships to students with consideration of the equity.